PENGARUH ARUS KAS TERHADAP LIKUIDITAS INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2009-2011 - MASAYU K, HANUM Masayu (Jurnal Akuntansi AKUNESA, 2013)
Reducing the inflation rate after the global financial crisis and declining interest rates areexpected to improve the liquidity of companies, especially consumer goods industry with goodcash flow management. This study aims to determine whether the cash flow effect on liquidity.This research uses descriptive quantitative method with cash flows from operating, investing andfinancing activities as an independent variable and liquidity as the dependent variable. Data is asecondary data from financial statements of consumer goods industry in Indonesian StockExchange. The results showed cash flow effect on liquidity and investing cash flows have anegative impact on liquidity of the consumer goods industry.Keywords : cash flow, liquidity